The Econometrics of Factor Loadings and Implications for Monetary Policy in a Small Open Economy (2005- 2020) – Sierra Leone - Christopher E. S. Warburton; Emerson Abraham Jackson (İktisat Politikası Araştırmaları Dergisi)
In this paper, the authors explored the interaction of macroeconomic variables with some form of vague interrelationships. The relevance of factor analysis has demonstrated an existing association between manifest and latent variables in helping the researchers come out with informed and justified suggestions that are relevant to inform effective policy decisions for the central bank action in Sierra Leone. We examine the relationships among some significant manifest and latent variables in a small open economy (Sierra Leone) using time series data spanning from 2005 to 2020. Both international crude oil prices and the local currency in circulation were found to be loadable under two factors (domestic and external), while the exchange rate was observed to be loaded under the external factor. The outcome also proved that the effects of domestic and international economic shocks (sudden but temporarily disrupted) converged (dissipated) after six to eight months. The paper concludes that innovation and energy diversification are important for domestic and external stability in a small open economy.